Administrative Issues and Challenges Faced by Higher Education Institutions (HEIs) - Mr. Sanjay Damor; Dr. Jigar V Patel (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Higher Education Institutions (HEIs) play a crucial role in the development of any nation by contributing to the workforce, knowledge economy, and social transformation. In India, as in many other countries, HEIs face numerous administrative challenges that hinder their ability to achieve academic excellence, innovation, and organizational efficiency. These challenges include complex governance structures, inadequate funding, political interference, rigid regulatory frameworks, and a lack of autonomy. This paper explores the primary administrative issues faced by HEIs in India, analyses the causes of these challenges, and offers potential solutions for creating a more effective and autonomous administrative framework within these institutions.
Keywords: Higher Education Institutions; Administrative Challenges; Governance; Autonomy; Funding; Regulatory Frameworks